Effects of a 5‐month football program on perceived psychological status and body composition of overweight boys. (August 2014) - Seabra, A. C.; Seabra, A. F.; Brito, J.; Krustrup, P.; Hansen, P. R.; Mota, J.; Rebelo, A.; Rêgo, C.; Malina, R. M.
Abstract : The effects of a 5‐month intervention of football instruction and practice on the perceived psychological status and body composition of overweight boys were examined. Twelve boys (8–12 years; body mass index ≥ 85th percentile) participated in a structured 5‐month football program, consisting of four weekly 60–90 min sessions with mean heart rate > 80%HRmax [football group (FG)]. A control group (CG) included eight boys of equivalent age from an obesity clinic located in the same area as the school. Both groups participated in two sessions of 45–90‐min physical education per week at school. Indicators of perceived psychological status included body image, self‐esteem, attraction to participation in physical activity, and perceived physical competence measured with standardized questionnaires. Body composition was evaluated using dual‐energy X‐ray absorptiometry. From baseline through 5 months, FG improved ( P < 0.05) in all indicators of psychological status (%Δ = +11.7 to +29.2%) compared with CG (%Δ = −32.1 to +0.5%). Changes in percentage body fat and lean body mass, however, did not differ between FG and CG. The findings suggest that a 5‐month football intervention program was effective in improving the psychological status of overweight boys but did not significantly alter body composition.